2021
DOI: 10.1037/xan0000288
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent evidence of extinction making acquisition context specific and ABA and ABC renewal effects in human predictive learning.

Abstract: Two experiments evaluated whether the experience of extinction makes acquisition context specific (EMACS) while the extinction learning itself also becomes context dependent under ABA and ABC renewal designs in a human predictive learning situation. Two groups of participants received X-Outcome pairings in context A followed by P-Outcome pairings in context B. For participants in group E, cue X was then extinguished in context B while cue P was trained. Participants in group NE were trained with P, but they di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 57 publications
2
11
0
Order By: Relevance
“…Experiment 1 found that extinction of a cue (E) made contextspecific retrieval of a different association (P-O) that was learned while cue E was extinguished in group EC12. This result replicates the EMACS effect reported by Callejas-Aguilera (2006, 2007) when the procedure was entirely conducted online with participants recruited from different countries and running the experiment in their own devices (see also Ogallar et al, 2019Ogallar et al, , 2021.…”
Section: Transparency and Opennesssupporting
confidence: 86%
See 4 more Smart Citations
“…Experiment 1 found that extinction of a cue (E) made contextspecific retrieval of a different association (P-O) that was learned while cue E was extinguished in group EC12. This result replicates the EMACS effect reported by Callejas-Aguilera (2006, 2007) when the procedure was entirely conducted online with participants recruited from different countries and running the experiment in their own devices (see also Ogallar et al, 2019Ogallar et al, , 2021.…”
Section: Transparency and Opennesssupporting
confidence: 86%
“…As that condition is not fulfilled in our experiments (P is never presented alone), to assume that contexts play the role of modulators in the EMACS effect would require us to accept that the modulatory role played by the contexts is different from the modulatory role played by discrete cues, as recent studies begin to suggest (see Balea et al, 2020). Alternatively, it is also possible that contextual control on extinction and EMACS effects would be exerted through different underlying mechanisms, even when they are found within the same situation, as reported by Ogallar et al (2021). Establishing the role played by the contexts when controlling performance in the EMACS effect would require of conducting specific tests that lay beyond the scope of this experimental series (see Nelson et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations